Integrating Tauhid Values into Entrepreneurial Leadership for Sustainable SME Performance in Malaysia - Sri Hartono; Nurizal Ismail; Riawan; Eka Indrayani (Universitas Muhammadiyah Ponorogo, 2026)
Introduction/Main Objecttives: This study aims to analyze the influence of tauhid-based entrepreneurial leadership on sustainable business performance among small and medium enterprises (SMEs) in Malaysia. Novelty: The study integrates the dimensions of habluminallah, habluminannas, and habluminal ‘alam into entrepreneurial leadership to develop a holistic Islamic leadership model oriented toward organizational sustainability. Research Methods: A quantitative explanatory approach was employed using a cross-sectional survey design. Data were collected from 248 SME owners and managers through structured questionnaires and analyzed using SmartPLS based Partial Least Squares Structural Equation Modeling (PLS SEM). Finding/result: The findings reveal that tauhid-based leadership significantly influences entrepreneurial leadership and sustainable business performance. Among the tauhid dimensions, habluminallah demonstrated the strongest influence on entrepreneurial leadership, followed by habluminannas and habluminal ‘alam. Furthermore, entrepreneurial leadership significantly affects sustainable business performance across economic, social, and environmental dimensions. The mediation analysis also confirms that entrepreneurial leadership significantly mediates the relationship between tauhid-based leadership and sustainable business performance. Conclusion: The study contributes theoretically by developing a multidimensional tauhid-based entrepreneurial leadership model integrating spirituality, entrepreneurship, and sustainability management within SMEs. Practically, the findings suggest that SME development strategies should integrate innovation capability with Islamic spiritual and ethical values to strengthen long term organizational sustainability.